Method of analyzing graphic representations based on verbal elements - Coelho Siqueira, Leonardo; Da Costa Braga, Marcos (InfoDesign, 2025)
This article presents a method for analyzing graphic representations of philosophical, literary, and artistic elements. In this regard, a methodological framework is established, integrating theoretical and analytical references to examine these elements in graphic manifestations. This paper will present the proposed method and examples of its application, as well as the protocols involved in the process and relevant reflections on its application. The proposed method of analysis has prior testing and validation, adhering to the semiotic principles of Charles Morris. It relies upon the works of scholars such as Luís Gomes et al. (2013), Ricardo Silva (2005), José Barros (2007), André Villas-Boas (2009), Priscila Farias (2016), and Evelyn Goldsmith (1984). Through this study, we have a validated analytical method in Leonardo Siqueira (2023), which synthesizes research techniques and guidelines for observing elements that might be graphically represented.